Management of Neuroendocrine Tumors: A Meeting of Experts from Latin America (2008)
A panel of experts from Latin America convened in Brazil, in May of 2007, for consensus recommendations regarding the management of neuroendocrine tumors (NETs) of the gastrointestinal tract and pancreas. The recently introduced World Health Organization classification of NETs represents a step forward, but the former classification of carcinoids into foregut, midgut and hindgut is still likely to be useful in the near future. Macroscopic description of the tumor should be followed by light microscopic examination and immunohistochemical staining, whereas other techniques might not be widely available in Latin America. Surgery remains the mainstay of treatment for patients with potentially curable tumors, and adequate selection is paramount in order to optimize treatment results. Regarding systemic therapy, patients with well-differentiated tumors or islet-cell carcinomas may be categorized as having indolent disease, while patients with poorly differentiated, anaplastic, and small-cell carcinomas, or with atypical carcinoids, may be approached initially as having aggressive disease. Somatostatin analogues play a cytostatic role in indolent tumors, and chemotherapy may play a role against other, more aggressive NETs. Obviously, there is an urgent need for novel therapies that are effective against NETs.